Phenotypic characterization of beta-lactamases producing Gram-negative bacteria in a tertiary hospital, Nepal - Maharjan, Elina; Shakya, Pooja; Bhattachan, Balkrishna; Baral, Bharat Prasad; Shrestha, Dhiraj (Nepal Journal of Biotechnology, 2019)
Infections caused by beta-lactamases producing Gram-negative bacteria are increasing, thus posing a challenge to the management of such infections. The surveillance data of such bacteria is limited in Nepal so this study aimed to detect the beta-lactamase producing Gram-negative bacteria in a tertiary setting. A total of 604 clinical samples, including urine, blood, sputum and body fluids, were cultured and identified by the routine standard laboratory protocols. Antibiotic susceptibility testing was done by Kirby Bauer disc diffusion method following Clinical and Laboratory Standard Institute guidelines (2014). Extended-spectrum beta-lactamases (ESBL) producers were identified by combined disk method and metallo-beta-lactamases (MBL) producers were identified by Imipenem- EDTA combined disk method. Out of 604 samples, 282 (46.7%) samples showed significant growth, of which 229 (81.2%) were Gram-negative bacteria. Of 229 Gram-negative bacteria, 200 (87.3%) were multidrug resistant, 67 (29.3%) were ESBL producers and 16 (7.0%) were MBL producers. Klebsiella pneumoniae were among higher ESBL producers and Pseudomonas aeruginosa were among higher MBL producers. The findings suggest higher antibacterial resistance among Gram-negative bacteria with the added burden of beta-lactamase production. Imipenem was effective against 125 of 229 Gram-negative bacteria tested. Thus, imipenem can be the drug of choice for empirical management. The higher multidrug resistance and higher beta-lactamases production among Gram-negative bacteria warrant the continuous monitoring, surveillance, early detection, and infection control practices of such bacteria